Trinidad and Tobago 1985 : a demographic analysis - Abdulah, Norma ed. (Caricom Secretariat GeorgetownGY, 1985)
Discusses the effects of changes in size and structure of the polulation on social and economic needs and capacity for production. Considers developments in education and how these have been affected by population growth and social and economic development. Deals with other issues such as internal migration and urbanization; mortality trends, fertility, household size and composition.